2021
DOI: 10.1037/ccp0000696
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial for identifying the most suitable treatment for depression based on patients’ attachment orientation.

Abstract: Objective: Many active treatments exist for major depressive disorder (MDD), but little is known about their differential effects for various subpopulations of patients to guide precision medicine. This is the first randomized controlled trial (RCT) designed to identify differential treatment effects based on patients' attachment orientations. We tested an a priori preregistered hypothesis of the potential moderating effect of patients' attachment orientation on the outcome of supportive therapy (ST) versus su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…In all supervisions, extensive use was made of video-taped sessions for feedback. As reported in the article detailing the main outcome of the trial (Zilcha-Mano et al, 2021), external observer coding of adherence revealed high adherence in both treatment conditions. The treatments were not found to differ in their efficacy or dropout level.…”
Section: Treatments and Therapistsmentioning
confidence: 76%
See 2 more Smart Citations
“…In all supervisions, extensive use was made of video-taped sessions for feedback. As reported in the article detailing the main outcome of the trial (Zilcha-Mano et al, 2021), external observer coding of adherence revealed high adherence in both treatment conditions. The treatments were not found to differ in their efficacy or dropout level.…”
Section: Treatments and Therapistsmentioning
confidence: 76%
“…Empirical research demonstrates the importance of disentangling the trait-like and state-like components of alliance (for review, see Zilcha-Mano & Fisher, 2022). Findings suggest that the trait-like alliance is at least partially a product of the patient's pretreatment characteristics, such as attachment style and interpersonal abilities (for a review, see Zilcha-Mano & Fisher, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given substantial meta-analytic evidence supporting the efficacy of PST (e.g., Barth et al, 2016) and indications of the importance of using supportive techniques and approaches in the treatment of perfectionism (e.g., Greenspon, 2014; Halgin & Leahy, 1989), we selected it as our active comparator. The use of supportive techniques to facilitate corrective emotional experiences is the focus of supportive treatment (Book, 1998; Leibovich et al, 2018; Rockland, 1989; Zilcha-Mano et al, 2021), and these principles are theorized to be salient in effecting change in patients with perfectionism (Ashby et al, 2005; Greenspon, 2014; Halgin & Leahy, 1989). Moreover, because DRT and PST are both rooted in psychodynamic principles, they share common elements, such as an emphasis on the therapeutic alliance, but differ in their use of exploratory/interpretive interventions.…”
Section: The Comprehensive Model Of Perfectionistic Behaviormentioning
confidence: 99%
“…For example, the PDT category includes a range of treatment modalities with different key techniques. A recent randomized controlled trial found that for patients with attachment anxiety, Supportive Expressive Therapy was more effective than Supportive Therapy (Zilcha-Mano et al, 2021). This finding suggests that treatment efficacy could be enhanced by utilizing expressive interventions with patients with this clinical profile.…”
Section: Reasons For Heterogeneitymentioning
confidence: 99%